Catalytic degradation of diclofenac from aqueous solutions using peroxymonosulfate activated by magnetic MWCNTs-CoFe3O4 nanoparticles. Issue 29 (28th May 2019) - Dadban Shahamat, Yousef; Zazouli, Mohammad Ali; Zare, Mohammad Reza; Mengelizadeh, Nezamaddin
Abstract : The MWCNTs-CoFe3 O4 as a novel catalyst showed high catalytic activity in activation of proxymonosulfate for degradation of diclofenac. Abstract : CoFe3 O4 nanoparticles supported on multi-walled carbon nanotubes (MWCNTs-CoFe3 O4 ) were synthesized by the co-precipitation method as a novel catalyst for degradation of diclofenac (DCF). The comparative experiments indicated that MWCNTs-CoFe3 O4 has a better catalytic activity in degradation of DCF and activation of peroxymonosulfate (PMS) compared to other catalytic systems. This can be attributed to the interaction of MWCNTs with CoFe3 O4 in accelerating the absorption process and activating the PMS ( E a = 22.93 kJ mol −1 ). The removal efficiencies of DCF and total organic carbon (TOC) were 99.04% and 50.11%, under optimum conditions, e.g., pH of 7, PMS dosage of 4 mM, DCF concentration of 30 mg L −1, catalyst dosage of 500 mg L −1, and reaction time of 120 min. The oxidation of DCF was fitted by the pseudo-first-order kinetic model and the constant rate was increased by increasing the pH, temperature, dosage of PMS and catalyst. The production of reactive species was studied using scavengers such as TBA and ethanol and the results showed that sulfate radical is the reactive species responsible for the degradation of DCF. The MWCNTs-CoFe3 O4 catalyst showed high stability and reusability based on five successful repeated reactions, X-ray diffraction and energy dispersive X-ray spectroscopy analysis. Based on the intermediates detected by gas chromatography-mass spectrometry (GC-MS), the possible pathways for DCF catalytic oxidation were proposed. The results explained that the PMS/MWCNTs-CoFe3 O4 system is a promising method for treating DCF solution due to high efficiency, good reusability of catalyst and greater PMS activation.